Long-term metformin adherence in the Diabetes Prevention Program Outcomes Study. Issue 1 (6th October 2020) - Walker, Elizabeth Arquin; Gonzalez, Jeffrey S; Tripputi, Mark T; Dagogo-Jack, Samuel; Matulik, Margaret J; Montez, Maria G; Tadros, Sameh; Edelstein, Sharon L
Abstract : Introduction: To investigate long-term metformin adherence in the Diabetes Prevention Program Outcomes Study (DPPOS) by examining: (1) predictors of long-term adherence to study metformin and (2) whether metformin adherence was associated with incident type 2 diabetes. Research design and methods: DPPOS was an open-label continuation of the randomized clinical trial (Diabetes Prevention Program (DPP)) in which eligible participants randomized to the metformin group were offered study metformin and followed over 11 years. A brief structured adherence interview was administered semiannually. Metformin adherence was assessed by pill counts. Predictors of metformin adherence were examined in multivariate regression models. Incident diabetes associated with metformin adherence and other variables was assessed in Cox proportional hazards models. Results: Of 868 participants eligible to continue taking study metformin, 664 (76%) took at least some metformin over 11 years, with 478 of them reporting problems with adherence. DPPOS cumulative adherence showed significant associations of higher adherence (≥80%) with early adherence at 3 months in DPP (p<0.001) and lower depression scores during DPPOS (p<0.001); significant differences were also seen by race/ethnicity (p<0.004). Predicting adherence by multivariate modeling showed odds of adherence significantly lower for Black participants and for participants reporting more than one barrier. Odds for adherence were significantly higher for those adherent early in DPP and those reporting at least one planned strategy to improve adherence. Higher metformin adherence was significantly associated with a lower diabetes risk (p=0.04), even after adjustment for demographic variables, depression, and anxiety scores. Conclusions: In this long-term diabetes prevention study, early metformin adherence and planned strategies to promote adherence improved long-term adherence over 11 years; higher adherence to metformin was related to lower diabetes incidence. Incorporating strategies to promote adherence when initially prescribing metformin and counseling to support adherence over time are warranted.